O PCC em São Paulo: "coletivo de presos" ou "organização criminosa"? - Moreira, Alex (2012)
The last two decades have brought changes to the state of São Paulo when it comes to public safety. The prison system in particular has undergone significant structural and functional changes. These transformations include: the large expansion plan of the prison system promoted by the state government; the exorbitant growth of the prison population; and birth and hegemony of PCC (First Command of the Capital) within the system. The proposal presented here is the study of the action of the government of São Paulo in the area of public safety front the actions of the First Command of the Capital inside and outside of prisons, to understand both the PCC phenomenon, as the reasons that made possible the emergence and strengthening this group precisely in the state of São Paulo.